Inteligensi Kultural Berbasis Etnomatematika pada Ragam Perlengkapan Tradisi Pernikahan Enis Konjo Sulawesi Selatan - Zulfiqar Busrah; Buhaerah Buhaerah; Andi Aras (Universitas Islam Ahmad Dahlan (UIAD) Sinjai, 2023)
This research is focused on exploring the concepts of geometry and algebra on the equipment used in Konjo ethnic weddings which are categorized in the aspects of artistic tools, sandan, boards and food. This research is a qualitative research with an ethnographic approach whose stages include determining the scope, determining and interviewing informants, documenting and recording, domain analysis, taxonomic analysis and ethnographic writing. Based on the exploration results it is found that the observed customary equipment can be modeled into a relationship between polynomial functions, such as the relationship of two parallel lines and two perpendicular lines in the balli' and kanre anak, a quadratic function rotated about the x-axis represents the gandrang pannahan model. The relationships of constant, linear and quadratic functions which are rotated about the y-axis produce the form of the gandrang jong. Furthermore, the concept of geometry can also be explored in the songkok recca as a sandan requirement whose surface is elliptical and the volume can be approximated using the concept of volume calculation using the slab approach. Whereas in the food aspect, there are beng-beng as dumplings for cucuru which can be represented as a constant function which is rotated around the x-axis. In the process of making the equipment explored it shows the ability, skills and mathematical activities in the form of counting, designing, measuring, locating and explaining. Mathematical concepts identified in customary equipment can be used as contextual learning resources in learning mathematics in formal education.